Pencatatan Harta Wakaf Dalam Perspektif Kemaslahatan Abu Ishaq Syatibi - Islami, Azka; Syarifuddin, Efi; Jajuli, M. Sulaeman (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
Syatibi, a prominent scholar of the Maliki school of thought, is considered a scholar who is very detailed and complete in discussing the concept of maslahat in Islamic law in his very popular book al-Muwafaqat. This normative juridical research examines the literature on the benefit of Syatibi as the core of this article, then tests it in its use on contemporary waqf issues, especially the regulations for registering waqf assets. He has clarified the benefits into two parts, the benefits from his existence in the world and from the aspect of his relationship with the shari'ah statements (kkitab shari'ah). In relation to its existence in the world, maslahat means something that talks about the upholding of human life and the achievement of everything that is held by its intellectual and emotional qualities. Therefore, in a practical sense, maslahat is closely related to something that is common in society, which is called adat. Meanwhile, from the second aspect, everything returns to the provisions of the shari'ah provisions. Through his views, he then analyzed the regulations for registering waqf assets in Indonesia. This normative research is then analyzed from the philosophy of Islamic law so that it is known that the registration of waqf assets remains consistent with the objectives of Islamic law to be enforced in Indonesia.